Evaluating Web and Mobile User Interfaces With Semiotics: An Empirical Study - Muhammad Nazrul Islam; Harry Bouwman; A. K. M. Najmul Islam (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Computer interface signs, such as navigational links, thumbnails, small images, command buttons, symbols, icons, etc., which serve as communication artifacts between designers/systems and users, constitute an under-researched area. To design and evaluate intuitive interface signs, the Semiotic Interface Sign Design and Evaluation (SIDE) framework was developed. The aim of this study is to test the framework & x2019;s applicability to evaluate web and mobile user interfaces. To that end, two empirical user studies were conducted among a total of 86 practitioners (n1 & x003D; 58, n2 & x003D; 28). The results show that the SIDE framework helps identify unique usability problems, such as the intuitiveness of interface signs in terms of their referential meaning, which would not have been detected with traditional heuristic evaluation methods. The paper increases our understanding of the intuitive nature of interface signs of web and mobile interfaces, and of the practical use of intuitive signs.